Determinan Penghindaran Pajak Di ASEAN Dengan Capital Intensity Sebagai Pemoderasi - Tambun, Sihar; Izzati, Elis Nur (Universitas 17 Agustus 1945 Jakarta, 2025)
This research aims to empirically examine the effect of thin capitalization, earnings management, and sales growth on tax avoidance with capital intensity as moderator. This research uses quantitative research. The data used in the following research is secondary data obtained from the ORBIS database version 349. The population in this research is all active manufacturing companies located in ASEAN countries in the period 2018 to 2022. The method used for determining the sample is purposive sampling method, and the number of samples obtained is 819 companies. Based on the results of the research conducted, there are several findings which can be concluded as follows: thin capitalization has no significant effect on tax avoidance; earnings management has a significant positive effect on tax avoidance; sales growth has no significant effect on tax avoidance; capital intensity is able to strengthen the effect of thin capitalization on tax avoidance; capital intensity is able to strengthen the positive effect of earnings management on tax avoidance; and capital intensity is able to strengthen the effect of sales growth on tax avoidance.